Relationship Between Urinary 4-(Methylnitrosamino)-1-(3-Pyridyl)-1-Butanol and Lung Cancer Risk in the General Population: A Community-Based Prospective Cohort Study - Park, Eun Young; Lim, Min Kyung; Park, Eunjung; Oh, Jin-Kyoung; Lee, Do-Hoon (Frontiers in Oncology, 2021)
No published studies have prospectively evaluated the association between urinary 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) levels and lung cancer risk in the general population. Here, we conducted a prospective community-based cohort study in the Republic of Korea to evaluate the relationship between urinary NNAL levels and lung cancer risk using prediagnostic urine samples. This prospective cohort study was based on the Korean National Cancer Center Community Cohort. During the follow-up period, 173 primary lung cancer cases were identified. Total urinary NNAL levels were measured by liquid chromatography-tandem mass spectrometry, and data were analyzed using multivariable Cox proportional hazards regression models. The risk of lung cancer was significantly increased per unit of natural log-transformed urinary NNAL (HR, 1.27; 95% CI, 1.09–1.48), after adjusting for age, region, entry year into the cohort, education achievement, alcohol consumption status, BMI, smoking status, and urinary cotinine levels. Cox proportional-hazards models with NNAL quartiles also showed positive dose-response relationships with risk of lung cancer. A significantly increased risk of lung cancer was found in the fourth quartile of urinary NNAL levels (HR, 3.27; 95% CI, 1.37–7.79, P for trend <0.01). After stratification with sex, the significant association remained in only men. Urinary NNAL levels are associated with the risk of lung cancer in the general population, and this association is independent from the quantification of cigarette smoking and nicotine uptake.